What is the most direct means to achieve strength gains specific to the demands of jumping events? - Kerin, D. (coachesinfo.com)
In an on-going effort to improve training methods for the athletes I coach, I have come across a number of articles regarding strength training for the jumping events. Much of what I find is the same basic information with a slightly different twist, often personalized with some applications or references specific to the author's experience. However this past year I have come across some very interesting articles that represent a fresh look at jumps-specific strength training. Independently, the articles suggest that the eccentric contraction that occurs at the plant, and strength training designed to improve this phase of a jumping action, might deserve greater consideration in the search for improvements in event performance. Intrigued with this new look at strength training for the jumps, I began the search for supporting information. With a little effort, I was able to obtain a wealth of information. In order to facilitate the presentation of information, it is assumed that an athlete is at an advanced level of training in areas of general strength, (isometric contractions/stabilization) as well as in the mechanics of jumping, performance of drills, etc. Event specific technique and neural considerations will not be addressed in this discussion.